1997
DOI: 10.1105/tpc.9.9.1683
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of the maize delta-zein and beta-zein genes results in stable accumulation of delta-zein in endoplasmic reticulum-derived protein bodies formed by beta-zein.

Abstract: Zeins, the major seed storage proteins of maize, are of four distinct types: (Y, p, S, and y. They are synthesized on the rough endoplasmic reticulum (ER) in a sequential manner and deposited in ER-derived protein bodies. We investigated the potential for producing sulfur-rich p-zein and 6-zein proteins in leaf and seed tissues by expressing the corresponding genes in a constitutive manner in transgenic tobacco. The 6-zein and @-zein, when synthesized individually, were stable in the vegetative tissues and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…It is possible that the proteins in this group all have a function in ER-derived protein body formation. Experiments that involved the transgenic expression of zeins in tobacco (Nicotiana tabacum) showed that ER-localized protein bodies can form, at least temporarily, in dicotyledons (Bagga et al, 1995(Bagga et al, , 1997Coleman et al, 1996Coleman et al, , 2004, and it is tempting to speculate that this is also possible in Arabidopsis. The group of proteins that are characterized by the presence of a signal peptide could function in protein scaffolding processes in other parts of the secretory system.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the proteins in this group all have a function in ER-derived protein body formation. Experiments that involved the transgenic expression of zeins in tobacco (Nicotiana tabacum) showed that ER-localized protein bodies can form, at least temporarily, in dicotyledons (Bagga et al, 1995(Bagga et al, , 1997Coleman et al, 1996Coleman et al, , 2004, and it is tempting to speculate that this is also possible in Arabidopsis. The group of proteins that are characterized by the presence of a signal peptide could function in protein scaffolding processes in other parts of the secretory system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, g-and b-zeins are not required for the normal accumulation of a-and d-zeins in maize endosperm. This was rather unexpected because in heterologous systems like tobacco (Nicotiana tabacum), a-and d-zeins could never accumulate at high levels unless they were coexpressed with the 27-kD g-or b-zein (Coleman et al, 1996;Bagga et al, 1997).…”
Section: Analysis Of the New Set Of Transgenic Seeds And Their Crossesmentioning
confidence: 99%
“…Expression of zeins in heterologous systems has been thought of as a test case for genetic engineering of nutritionally improved seeds. But when an attempt was made to express single a-or d-zein gene copies in tobacco endosperm, zein proteins failed to accumulate unless coexpressed with g-or b-zein (Coleman et al, 1996(Coleman et al, , 2004Bagga et al, 1997;Hinchliffe and Kemp, 2002). These findings indicated that a-zein or d-zein in tobacco was prone to degradation and that coexpression of Cys-rich g-or b-zein, which could initiate protein body formation alone, stabilized a-or d-zein by sequestering them into protein bodies.…”
Section: Need Of Homologous Expression Systems To Validate Gene Functionmentioning
confidence: 99%
“…Previous studies investigating the heterologous expression of zein subgroups alone or in combination have shown that the presence and balanced interaction of all zein subfamilies is necessary to stabilize the zein bodies and form typical spherical structures. Thus, although δ-zein [42], β-zein (re-assigned to the γ-zein subfamily [31]) [43], and γ-zein [28] can form protein aggregates by themselves, these do not form typical zein bodies. For example, α-zein forms stable protein bodies when expressed in Xenopus laevis oocytes but not in tobacco leaves, but typical protein body structures are formed ectopically when different zein subtypes are coexpressed [44].…”
Section: Insoluble 2g12 Accumulates Due To Covalent Interactions Withmentioning
confidence: 92%